Effect of Prolonged Exposure, intensified Prolonged Exposure and STAIR+Prolonged Exposure in patients with PTSD related to childhood abuse: a randomized controlled trial. Issue 1 (1st January 2021) - Oprel, Danielle A. C.; Hoeboer, Chris M.; Schoorl, Maartje; Kleine, Rianne A. de; Cloitre, Marylene; Wigard, Ingrid G.; van Minnen, Agnes; van der Does, Willem
ABSTRACT: Background : It is unclear whether the evidence-based treatments for PTSD are as effective in patients with CA-PTSD. Objective : We aimed to investigate the effectiveness of three variants of prolonged exposure therapy. Method : We recruited adults with CA-PTSD. Participants were randomly assigned to Prolonged Exposure (PE; 16 sessions in 16 weeks), intensified Prolonged Exposure (iPE; 12 sessions in 4 weeks followed by 2 booster sessions) or a phase-based treatment, in which 8 sessions of PE were preceded by 8 sessions of Skills Training in Affective and Interpersonal Regulation (STAIR+PE; 16 sessions in 16 weeks). Assessments took place in week 0 (baseline), week 4, week 8, week 16 (post-treatment) and at a 6-and 12-month follow-up. The primary outcome was clinician-rated PTSD symptom severity. Results : We randomly assigned 149 patients to PE (48), iPE (51) or STAIR+PE (50). All treatments resulted in large improvements in clinician assessed and self-reported PTSD symptoms from baseline to 1-year follow-up (Cohen's d > 1.6), with no significant differences among treatments. iPE led to faster initial symptom reduction than PE for self-report PTSD symptoms ( t 135  = −2.85, p = .005, d = .49) but not clinician-assessed symptoms (t135  = −1.65, p = .10) and faster initial symptom reduction than STAIR+PE for self-reported ( t 135  = −4.11, p < .001, d = .71) and clinician-assessed symptoms ( t 135  = −2.77, p = .006, Cohen's d = .48) STAIR+PE did not result in significantly more improvement from baseline to 1-year follow-up on the secondary outcome emotion regulation, interpersonal problems and self-esteem compared to PE and iPE. Dropout rates did not differ significantly between conditions. Conclusions : Variants of exposure therapy are tolerated well and lead to large improvements in patients with CA-PTSD. Intensifying treatment may lead to faster improvement but not to overall better outcomes. The trial is registered at the clinical trial registry, number NCT03194113, https://clinicaltrials.gov/ct2/show/NCT03194113 HIGHLIGHTS: Childhood abuse-related PTSD can be effectively treated with (variants of) exposure therapy. STAIR+PE and intensified PE did not improve treatment outcomes compared to PE. Intensified PE showed faster symptom improvement.